Therapeutic potential of gut microbiota modulation in epilepsy: A focus on short-chain fatty acids - Rong Yan; Linhai Zhang; Ya Chen; Yongsu Zheng; Ping Xu; Zucai Xu (Neurobiology of Disease)
According to the criteria established by the International League Against Epilepsy (ILAE), epilepsy is defined as a disorder characterized by at least two unprovoked seizures occurring more than 24 h apart. Its pathogenesis is closely related to various physiological and pathological factors. Advances in high-throughput metagenomic sequencing have increasingly highlighted the role of gut microbiota dysbiosis in epilepsy. Short-chain fatty acids (SCFAs), the major metabolites of the gut microbiota and key regulators of the gut-brain axis, support physiological homeostasis through multiple mechanisms. Recent studies have indicated that SCFAs not only regulate seizures by maintaining intestinal barrier integrity and modulating intestinal immune responses, but also affect the structure and function of the blood-brain barrier (BBB) and regulate neuroinflammation. This review, based on current literatures, explores the relationship between SCFAs and epilepsy, emphasizing how SCFAs affect epilepsy by modulating the intestinal barrier and BBB. In-depth studies on SCFAs may reveal their therapeutic potential and inform the development of gut microbiota-targeted epilepsy treatments.